Genetic parameters for dystocia, milk yield and age at first calving in Brazilian Holstein cows - Stefani, Gabriela [UNESP] (2021)
The present study aims to estimate genetic parameters for dystocia, milk yield and age at first calving of Holstein cows reared in intensive production systems located in the southeastern region of Brazil. A total of 26,987 first-lactation records of Holstein cows were used. The following traits were analysed: 305-day cumulative first lactation milk yield (MY305), age at first calving (AFC) and dystocia. Dystocia was defined as a binary trait, with 0 indicating failure and 1 indicating success. Success was attributed to cows that had a normal calving, and failure was attributed to cows that had a difficult or human-assisted parturition. The (co)variance components were estimated using a Bayesian approach. The heritability estimates were 0.15 (0.01), 0.27 (0.02), and 0.17 (0.03) for MY305, AFC and dystocia, respectively. Dystocia showed genetic correlations of 0.30 (0.09) with AFC and −0.17 (0.11) with MY305. Early maturing heifers may be genetically prone to a more difficult first calving.